Modular Strategies for Structure and Function Employed by Marine Cyanobacteria: Characterization and Synthesis of Pitinoic Acids - Montaser, Rana (2013)
[Image: see text] Novel bioactive lipids were identified from a Guamanian cyanobacterium; the Pseudomonas aeruginosa quorum sensing inhibitor pitinoic acid A (1) and the anti-inflammatory pitinoic acids B (2) and C. The structure of 2 was confirmed by synthesis, which also allowed for biological evaluation. Since 2 is an ester of pitinoic acids A and C, it represents a prodrug strategy to liberate dual biological activity for the management of P. aeruginosa infections and their associated inflammation.